2009
DOI: 10.1111/j.1365-2230.2008.03008.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilic syndrome with various skin lesions and juvenile temporal arteritis

Abstract: Hypereosinophilic syndrome (HES) is a multisystem disease with a high mortality rate. It is characterized by peripheral blood eosinophilia and eosinophilic infiltration of the skin and many other organs. The commonest cutaneous features include erythematous pruritic maculopapules and nodules, angio-oedema or urticarial plaques. However, some case reports have indicated that eosinophilic cellulitis, cutaneous necrotizing eosinophilic vasculitis, Raynaud's phenomenon and digital gangrene may also occur as cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Although mild eosinophilia is common, marked eosinophilia is rare in many of the other vasculitides but has been seen in patients with cutaneous necrotizing vasculitis, thromboangiitis obliterans with eosinophilia of the temporal arteritis [74] and in Wegener's granulomatosis. [75]…”
Section: Hypereosinophilia With Organ-restricted Involvementmentioning
confidence: 99%
“…Although mild eosinophilia is common, marked eosinophilia is rare in many of the other vasculitides but has been seen in patients with cutaneous necrotizing vasculitis, thromboangiitis obliterans with eosinophilia of the temporal arteritis [74] and in Wegener's granulomatosis. [75]…”
Section: Hypereosinophilia With Organ-restricted Involvementmentioning
confidence: 99%
“…Eosinophilia was a striking feature in JG and influenced extended serological testing. Although there is a link between hyper-eosinophilic syndrome and juvenile temporal arteritis [55], there are no strong clinical associations between peripheral blood eosinophilia and adult GCA [56]. The eosinophilia in our case may have simply reflected the general elevation in inflammatory cell milieu.…”
Section: Discussionmentioning
confidence: 72%
“…These patients complained of painless nodules on their temple, and the pathologic findings revealed nongiant cell inflammation of temporal arteries [4]. From then on until February 2019, according to our literature review through PubMed and Scopus, 18 more cases have been reported [23567891011121314151617181920]. Including the present case, a total of 23 cases of JTA were reported and their mean age was 27 years (range, 7 to 44 years) and there was the male predominance (18 men and 5 women).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one of the recurred cases reported that eosinophil count was elevated at recurrence [18]. Although only a small number of cases were available for the trend of eosinophil count after excision [8131819], eosinophilia may persist even if temporal arteritis improves without systemic steroids, and may lead to recurrence because documented recurrences occurred only in the patients with JTA with eosinophilia who treated locally. According to very recent case series (n = 12) from France, 41.7% (5 of 12) had peripheral eosinophilia, and this figure was similar to our estimate of 43.4% (10 of 23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation